2009
DOI: 10.4049/jimmunol.0800471
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Therapeutic Synergy of IL-27 and IL-2: Enhancement of T Cell Sensitization, Tumor-Specific CTL Reactivity and Complete Regression of Disseminated Neuroblastoma Metastases in the Liver and Bone Marrow

Abstract: IL-27 exerts antitumor activity in murine orthotopic neuroblastoma, but only partial antitumor effect in disseminated disease. This study demonstrates that combined treatment with IL-2 and IL-27 induces potent antitumor activity in disseminated neuroblastoma metastasis. Complete durable tumor regression was achieved in 90% of mice bearing metastatic TBJ-IL-27 tumors treated with IL-2 compared with only 40% of mice bearing TBJ-IL-27 tumors alone and 0% of mice bearing TBJ-FLAG tumors with or without IL-2 treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 65 publications
(76 reference statements)
1
63
0
Order By: Relevance
“…Interleukin-15 (IL-15) is a cytokine that facilitates CD8 ϩ and CD4 ϩ effector T cell expansion while having no preferential effect on the proliferation of Tregs (67). In addition, IL-27 delivery inhibits CD4 ϩ CD25 ϩ Foxp3 ϩ Treg expansion and potentiates tumor-specific CTL reactivity (68). Based on these properties, it is reasonable to speculate that therapeutic IL-15 and IL-27 administration might lead to lower levels of Tregs and higher levels of effector T cells in lymphoid tissues, and thus lead to improved viral control.…”
Section: Specific Cd8mentioning
confidence: 99%
“…Interleukin-15 (IL-15) is a cytokine that facilitates CD8 ϩ and CD4 ϩ effector T cell expansion while having no preferential effect on the proliferation of Tregs (67). In addition, IL-27 delivery inhibits CD4 ϩ CD25 ϩ Foxp3 ϩ Treg expansion and potentiates tumor-specific CTL reactivity (68). Based on these properties, it is reasonable to speculate that therapeutic IL-15 and IL-27 administration might lead to lower levels of Tregs and higher levels of effector T cells in lymphoid tissues, and thus lead to improved viral control.…”
Section: Specific Cd8mentioning
confidence: 99%
“…IL-27 is a heterodimeric anti-inflammatory cytokine composed of EBI3 and p28, which regulates Th cell function during autoimmune and pathogen-induced immune responses (1,3,4). IL-27 exhibits various therapeutic capabilities, such as regulating antiviral ability (12,13), enhancing antitumor immune responses (14), directing antiproliferative effects on tumors (15)(16)(17), and reducing the inflammation associated with experimental autoimmune arthritis (18,19). Serum IL-27 triggers an earlier immune response to prevent hepatic injury in different clinical-pathologic stages of HBV-infected patients (50).…”
Section: Il-27 Enhances the Expression Of Ifn-l1 Receptors Il-28r1 Anmentioning
confidence: 99%
“…Overexpressing IL-27 decreases regulatory T cell frequencies, induces spontaneous inflammation, and activates proliferation of naive human B cells and CD4 + T cells (10,11). IL-27 has therapeutic potential through various mechanisms: inhibiting replication of HIV (12) and hepatitis C virus (HCV) (13), enhancing antitumor immune responses (14), directing antiproliferative effects on tumors (15)(16)(17), and reducing the inflammation associated with experimental autoimmune arthritis (18,19). We recently demonstrated that during influenza A virus (IAV) infection, IL-27 is strongly induced through cyclooxygenase-2 (COX-2)-and protein kinase A (PKA)-signaling pathways (20).…”
mentioning
confidence: 99%
“…Cytokines such as interleukin-2 (IL-2), IL-12 [36], and IL-27 [37] either as a single agent or in combination have demonstrated antitumor efficacy in preclinical neuroblastoma models.…”
Section: Vaccinesmentioning
confidence: 99%